Low-dose aspirin, coxibs, and other NSAIDS: a clinical mosaic emerges. - Patrono, C; Baigent, C (2009)
Aspirin has been a commercial drug for over a century, although for most of this history, an understanding of its mechanism of action, as an inhibitor of cyclooxygenase (COX) activity and thus of prostanoid synthesis, was lacking. Over the past fifty years, a large number of other nonsteroidal antiinflammatory drugs (NSAIDs) have been developed, and a much deeper understanding of inflammation and prostanoid action has emerged. Indeed, a new class of selective inhibitors of the cyclooxygenase-2 isozyme was introduced, about ten years ago, and these so-called coxibs quickly became regarded as preferable, in certain clinical contexts, to avoid side effects associated with the use of aspirin and previously developed NSAIDs. This regard for coxibs has been challenged, sometimes infamously, as cardiovascular events associated with coxib use have become apparent. A variety of clinical trials have led to seemingly conflicting data concerning the roles of COX-1 and COX-2, and the implications of their relative inhibition, in cardiovascular health and disease. In this Review, the authors offer an assessment of drug pharmacokinetics and enzyme physiology that reconciles cardiovascular appraisals from a wide array of clinical data.